The characterization of care that generates obstetric violence to parturient women: an integrative review (Research, Society and Development, 2021)
Objective: Literature analysis on the characterization of obstetric violence suffered by parturients in childbirth care. Methods: This is an integrative literature review with a qualitative approach. Based on materials available in the Virtual Health Library. Articles published from 2016 to 2021, in full text, in Portuguese, Spanish and English, that related to the proposed theme, were selected. Results and discussion: The final sample consists of 14 articles, 9 from LILACS, 3 from BDENF and 2 from MEDLINE. A thorough reading was analyzed and discussed in accordance with the topic presented. To carry out the analysis and discussion of this research, the following study variables were initially evaluated: authors, federative unit, year of publication, title, journal and database. The results are grouped into thematic axes, in three categories: “The view of women about their rights in childbirth”; “Most recurrent invasive procedures among them”; “Forms of violence suffered among parturient women”. Conclusion: The study hopes to contribute to future research in the health area focusing on the performance of professionals with care for parturients, in addition to awakening students and professionals in the area to encourage and consequently enable satisfactory changes that enhance the performance and positive growth of the profession.